Dermatofibrosarcoma Protuberans Of the Vulva Treated with Mohs Micrographic Surgery (2019)
Dermatofibrosarcoma protuberans (DFSP) of the vulva is extremely rare conditions. It has been published approximately 43 case reports in medical literature; most tumors arise on the labia majora. We present a 57-year-old woman with DFSP in vulva that was removed by Mohs Micrographic Surgery technique. The wound exhibited a satisfying functional and cosmetic appearance, with no evidence of deformity of the vulva.